Effects of oral administrations of pomegranate seed extract on surgical wound healing in rabbits - Kandemir, F. M.; Sagliyan, A.; Ozkaraca, M.; Gunay, C.; Han, M. C.; Benzer, F. (Ecole Nationale Veterinaire Toulouse, 2013)
This study examined the effects of orally given pomegranate seed extract (PSE) on healing of surgically induced full thickness skin wounds in terms of clinical, histopathological and biochemical aspects. A total of 48 healthy, adult male New Zealand rabbits were randomly divided in 2 equal experimental (PSE group) and control groups (C): one week prior the surgery, 100 mg/kg per day via gastric catheter pomegranate seed extract was orally given for 20 days to the assay animals. After one week, all rabitts were anaesthetized by intramuscular injection of xylazine HCl (5 mg/kg) and ketamine HCI (50 mg/kg) and after shaving and disinfection, a circular full thickness skin defect of 2.5 cm diameter was incised on the median line of the back area. Macroscopic and histopathological aspects as well as the tissue oxidant/antioxidant balance were determined on 6 rabbits from each group slaughtered at the 5th, 10th, 15th and 20th days post-surgery.
Keywords: Wound healing; pomegranate seed extract; free radical; antioxidant status